Implementing Value Co-Creation by Developing Service Dominant Logic Through Telkom Marketing Content Innovation Program - Ujiati, Nurul Nugraheni Ratna; Marsasi, Endy Gunanto (SENTRALISASI, 2024)
The objective of this study is to examine the digital innovation and marketing strategies employed by PT Telkom Indonesia in order to gain a competitive advantage within the telecommunications industry. The research method is descriptive qualitative, with data collected through interviews, observation, and content analysis. The research demonstrates that PT Telkom Indonesia has effectively developed a digital marketing program that enhances customer productivity and innovation. However, there are still some areas that require improvement, such as social media content planning. The implementation of Value Co-Creation (VCC) and Service Dominant Logic (SDL) strategies has been shown to be effective in increasing customer loyalty and strengthening the company's position in a competitive market. This research offers a significant contribution to the understanding of effective marketing strategies in the telecommunications industry. Based on the results of this study, practical recommendations for the optimization of PT Telkom Indonesia's digital marketing can be considered.